Re-Thinking Q.S An-Nisa Ayat 11 (Pendekatan Hermeneutika Asghar Ali Engineer) - Muhammad Hasnan Nahar (AL-MUFASSIR, 2021)
The distribution of inheritance for Arabs is based on two basic principles, namely the principle of nasab for heredity and the principle of sabab for adoption of children, both of these are only for men, then Islam comes to give inheritance rights to women, written in QS An-Nisa verse 11. Islamic law regarding the distribution of inheritance is included in the category of verses that must be re-thought, with the view that there will always be something that changes at any time with the emergence of various problems and various challenges in its implementation. By using hermeneutics Ashgar Ali Engineer, the original division of inheritance between men and women are 2: 1, so with the demands of justice, the demand for men can be equal to women, or even women get more.